2020
DOI: 10.3389/fmicb.2020.575625
|View full text |Cite
|
Sign up to set email alerts
|

Plant Genotype Influences Physicochemical Properties of Substrate as Well as Bacterial and Fungal Assemblages in the Rhizosphere of Balsam Poplar

Abstract: Abandoned unrestored mines are an important environmental concern as they typically remain unvegetated for decades, exposing vast amounts of mine waste to erosion. Several factors limit the revegetation of these sites, including extreme abiotic and unfavorable biotic conditions. However, some pioneer tree species having high levels of genetic diversity, such as balsam poplar (Populus balsamifera), can naturally colonize these sites and initiate plant succession. This suggests that some tree genotypes are likel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…DNA was extracted from 250 mg of homogenised soil using the DNeasy PowerSoil Pro kit and the QIAcube® (Qiagen, Germany) automated platform. 16S rRNA and ITS2 libraries were prepared following 64 , except that the first set of PCR reactions were set up by mixing 25 μL of HotStarTaq Plus Master Mix, 19 µL RNase-Free Water (Qiagen, homogenised), 0.5 μL of 10 μM primer and 5 μL of gDNA at 5 ng μL -1 . Indexed and purified amplicons were quantified using the Synergy™ Mx Microplate Reader (BioTek Instruments, USA) before pooling at equimolar concentration.…”
Section: Environmental Predictors Of Dommentioning
confidence: 99%
“…DNA was extracted from 250 mg of homogenised soil using the DNeasy PowerSoil Pro kit and the QIAcube® (Qiagen, Germany) automated platform. 16S rRNA and ITS2 libraries were prepared following 64 , except that the first set of PCR reactions were set up by mixing 25 μL of HotStarTaq Plus Master Mix, 19 µL RNase-Free Water (Qiagen, homogenised), 0.5 μL of 10 μM primer and 5 μL of gDNA at 5 ng μL -1 . Indexed and purified amplicons were quantified using the Synergy™ Mx Microplate Reader (BioTek Instruments, USA) before pooling at equimolar concentration.…”
Section: Environmental Predictors Of Dommentioning
confidence: 99%
“…DNA was quantified with the Qubit dsDNA HS Assay Kit on a Qubit 3.0 Fluorometer (Thermo Fisher Scientific, Waltham, MA, USA). Amplicon library preparation for Illumina sequencing of the ITS2 region of the fungal ribosomal DNA was performed as previously described in Rheault, et al [31]. Briefly, the polymerization chain reaction (PCR) is first used to amplify the target fungal DNA, and the success of the PCR is validated by gel electrophoresis.…”
Section: Dna Analysismentioning
confidence: 99%
“…A second purification step is then performed before samples are normalized, pooled, and sequenced on an Illumina MiSeq system (Illumina, San Diego, CA, USA). Following DNA sequencing, bioinformatic analysis was carried out in QIIME (version 1.9.1 [32]) as previously described [31] to generate alpha and beta diversity metrics and taxa summary tables. The rarefaction was fixed at 3100 sequences per sample, which allowed us to keep 91 of the 92 samples in the analysis.…”
Section: Dna Analysismentioning
confidence: 99%
“…Researchers have also demonstrated that the seed‐associated microbial community is affected by factors such as crop, plant genotype, and environmental conditions (Morales Moreira et al., 2021). Apart from affecting the physicochemical properties of substrate, the plant genotype was also found to regulate the rhizosphere fungal and bacterial communities associated with Balsam poplar ( Populus balsamifera L.) (Rheault et al., 2020). Host genotype‐dependent selection of microbial community has been also reported (Morella et al., 2020) and the rhizosphere microbial community profiles have been linked to genotypic characteristics of plants (Lumibao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%